Depth of invasion in early stage oral cavity squamous cell carcinoma: The optimal cut-off value for elective neck dissection. (December 2020) - van Lanschot, Cornelia G.F.; Klazen, Yoram P.; de Ridder, Maria A.J.; Mast, Hetty; ten Hove, Ivo; Hardillo, José A.; Monserez, Dominiek A.; Sewnaik, Aniel; Meeuwis, Cees A.; Keereweer, Stijn; Aaboubout, Yassine; Barroso, Elisa M.; et al.
Highlights: Depth of invasion (DOI) is associated with lymph node metastasis in oral cancer (OC). The AJCC (8th edition) definition of DOI in OC is recommended. DOI ≥ 4 mm is an accurate cut-off value for elective neck dissection (END). END performed for patients with DOI ≥ 4 mm results in lower regional recurrence. Abstract: Objectives: Depth of invasion (DOI) is the most important predictor for lymph node metastasis (LNM) in early stage (T1-T2) oral cancer. The aim of this study is to validate the cut-off value of 4 mm on which the decision to perform an Elective Neck Dissection (END) is made. Materials and methods: We performed a retrospective study in patients with pathologically proven early stage oral cavity squamous cell carcinoma (OCSCC) without clinical or radiological signs of LNM, who were treated between 2013 and 2018. An END was performed when DOI was ≥ 4 mm and a watchful waiting protocol was applied in patients with DOI < 4 mm. Results: Three hundred patients were included. END was performed in 77% of patients with DOI ≥ 4 mm, of which 36% had occult LNM (pN+). Patients in the watchful waiting group (48%) developed a regional recurrence in 5.2% for DOI < 4 mm and 24.1% for DOI ≥ 4 mm. For DOI ≥ 4 mm, regional recurrence free survival was higher for patients who were treated with END compared to watchful waiting (p = 0.002). A Receiver-Operator-Curve -analysis showed that a DOI cut-off value of 4.0 mm was the optimal threshold for the prediction of occult LNM (95.1% sensitivity, 52.9% specificity). Conclusion: A DOI of ≥ 4 mm is an accurate cut-off value for performing an END in early stage OCSCC. END results in higher survival rates and lower regional recurrence rates in patients with DOI ≥ 4 mm.